2020
DOI: 10.36547/nbc.v19i2.776
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of curd spread with different flax oil content

Abstract: The creation of new types of dairy products for functional purposes with the addition of unconventional oils as sources of polyunsaturated fatty acids (PUFA) is a promising and relevant research sphere. The study aimed to investigate the fatty acid composition of experimental samples of curd spread with different content of flax oil. The fatty acid composition was determined on a Hewlett Packard HP-6890 chromatograph with a flame ionization detector equipped with a 100 m long SP-2560 capillary column. It is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
2
0
6
Order By: Relevance
“…In general, more and more data have recently appeared, and research was conducted on the enrichment of various types of cheese [48], [49] with vegetable oils to improve their lipid composition [64], [65]. The addition of oils, particularly linseed, is a perspective in developing recipes for new types of products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, more and more data have recently appeared, and research was conducted on the enrichment of various types of cheese [48], [49] with vegetable oils to improve their lipid composition [64], [65]. The addition of oils, particularly linseed, is a perspective in developing recipes for new types of products.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, adding flax seeds and flax flour slightly enhanced the development of the cheese's bifidobacteria and lactic acid microflora. Enrichment of such dairy products as yogurt and curd paste with linseed oil did not influence microbiological processes during production and storage [48], [49]. At the same time, researchers [67] showed that adding linseed mucilage to cream cheese increased protein, ash, and total solids content, while moisture content and pH values decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Розробка нових рецептур майонезів і їх технологій залишається актуальним питанням з позиції нормування власне жирнокислотного складу раціону людини (Bondarenko, 2013;Helikh et al, 2021). Перспективної уваги в цьому плані заслуговує лляна і конопляна олії як джерела ПНЖК родини омега-3 (α-ліноленова кислота) та ПНЖК родини омега-9 (олеїнова кислота) (Goyal et al, 2014;Lewinska et al, 2015;Lialyk et al, 2019;2020).…”
Section: вступunclassified
“…Особливої уваги в цьому плані заслуговує лляна олія, як найбільше джерело ПНЖК родини омега-3 (α-ліноленова кислота) і яка успішно використовується у виробництві різних функціональних продуктів (Goyal et al, 2014;Lewinska et al, 2015;Lialyk et al, 2019;2020).…”
Section: вступunclassified